P311 Deficiency Leads to Attenuated Angiogenesis in Cutaneous Wound Healing - Wang, Song; Zhang, Xiaorong; Qian, Wei; Zhou, Daijun; Yu, Xunzhou; Zhan, Rixing; Wang, Ying; Wu, Jun; He, Weifeng; Luo, Gaoxing (Frontiers in Physiology, 2017)
P311 was identified to markedly promote cutaneous wound healing by our group. Angiogenesis plays a key role in wound healing. In this study, we sought to define the role of P311 in skin wound angiogenesis. It was noted that P311 was expressed in endothelial cells in the dermis of murine and human skin wounds. The expression of P311 was confirmed in cultured murine dermal microvascularendothelial cells (mDMECs). Moreover, it was found that knockout of P311 could attenuate the formation of tubes and motility of mDMECs significantly in vitro. In the subcutaneous Matrigel implant model, the angiogenesis was reduced significantly in P311 knockout mice. In addition, wound healing was delayed in P311 knockout mice compared with that in the wild type. Granulation tissue formation during the defective wound healing showed thinner and blood vessel numbers in wound areas in P311 knockout mice were decreased significantly. A reduction in VEGF and TGFβ1 was also found in P311 KO mice wounds, which implied that P311 may modulate the exprssion of VEGF and TGFβ1 in wound healing. Together, our findings suggest that P311 plays an important role in angiogenesis in wound healing.